UJI VALIDITAS DAN PRAKTIKALITAS LKPD BERORIENTASI PROBLEM BASED LEARNING TERINTEGRASI NILAI-NILAI ISLAM PADA TOPIK EKOSISTEM DI MADRASAH ALIYAH - Azhari, Azhani; Zulyusri, Zulyusri; Ardi, Ardi; Rahmi, Fitri Olvia (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The implementation of the Independent Curriculum in Islamic educational institutions is an important step in integrating Islamic values with learning activities. One of the relevant learning models is Problem Based Learning (PBL) integrated with Islamic values into learning media. This research is included in the type of development research (RD) which aims to develop Student Worksheets (LKPD) oriented towards PBL integrated with Islamic values on ecosystem material for Phase E students at Madrasah Aliyah which are valid and practical. This study uses the Four-D (4D) development model. The subjects of the study involved two Biology lecturers from FMIPA UNP, a biology teacher, and 36 Phase E students at MAN 2 Payakumbuh. The data were analyzed using qualitative and quantitative descriptive methods. The study produced a PBL-oriented LKPD integrated with Islamic values on ecosystem material. The validity test by experts showed an average score of 95.42% which is included in the very valid category. The practicality test by teachers and students obtained an average of 91.97%, also included in the very practical category. Thus, this LKPD is declared very valid and very practical, and is suitable for use as a biology learning medium.